PENGARUH JENIS TANAH DAN KONSENTRASI ASAP CAIR TERHADAP PERTUMBUHAN SERTA HASIL TANAMAN LOBAK PUTIH DAN MERAH - Arnanto, Driska; Hanggara Putra, Leo; Sunaryo, Yacobus; Santoso, Budi (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2023)
This study aims to determine the concentration of liquid smoke on the growth and yield of white and red radishes. Knowing the best type of soil by giving the concentration of liquid smoke for the growth and yield of red and white radishes. Knowing the type of radish that gives the best radish growth and yield. The research was carried out at the UPTD Bantul Agricultural Seed Center on Mindi Street, Ngentak Hamlet, Sumberagung Village, Kapanewon Jetis, Bantul Regency, Special Region of Yogyakarta starting in October 2022 - January 2023. This research was a factorial experiment consisting of 3 factors. The first factor is the type of soil, the concentration of liquid smoke, and the type of horseradish. Based on the results of the study, it can be concluded that the Mediterranean soil type treatment gave better results than the red-yellow podzolic soil. Treatment of liquid smoke concentration of 1% and 3% gave the same results. This type of white radish plant gives better growth and yield than the red radish type